Detection of Helicobacter Pylori in Saliva and Oral Swab Versus Biopsy Samples Using Urease Test, Culture, PCR Technique - Duha Sadiq Abbas, Thanaa Rasheed Abdulrahman, Sajed Ali Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
The aim of this study was to compare between different methods in identifying Helicobacter pylori in saliva, oral swabs and biopsy specimens obtained from patients’ chronic gastritis and peptic ulcer disease. Methods: A total of 100 tissue biopsy, saliva and oral swab samples were collected and tested for identification of H. pylori using urease test, culture media and PCR for detection of 16sRNA and virulence CagA and VagA genes. Results: It was found that the biopsy results in all methods have high percentage 85% with the exception of CagA gene that gave a high percentage 71% in saliva samples, there were 82.05% urease positive using saliva sample and 43.59% using swab sample, 59.65% positive saliva culture and 38,60% positive swab culture, regarding 16sRNA, there were 70.59% saliva sample positive and 43,53% positive swab sample. H pylori detection by cag A gene of saliva in comparison with biopsy was 87.50% and of oral swab 41.67%, however by VagA gene the result of saliva was 31.25% and of oral swab was 16.67%. Conclusion: All detection method that done by using biopsy sample more accurate and give reliable result. Saliva sample using in detection H.pylori is attractive for use in population based prevalence surveys for H. pylori infection.